Alpu kreimules herbāriji Latvijas Universitātes Muzejā - Jamonte, Daiga (My University, 1922)
Alpu kreimule Pinguicula alpina L. ir rets augs, kurš šobrīd vairs nav sastopams Latvijas flora. Tā vienīgā dabīgā augtene bija uz Staburaga Daugavas krastā. Pļaviņu HES būvniecibas rezultātā tā tika iznīcināta. Latvijas Universitātes Muzeja herbārijā Botānikas un mikoloģijas kolekcijās glabājas šā auga herbāriji gan no Latvijas, gan Igaunijas. Šeit atrodas gan senākais ievāktais herbārijs uz Staburaga, gan pēdējais, kas tika šeit ievākts 1961. gadā.

Alpine butterwort Pinguicula alpina L. is a rare plant that is no longer present in the Latvian flora. Its only natural place of growth was on Staburags on the coast of Daugava. As a result of the construction of Plavinas HPP, it was destroyed. The herbarium of the Museum of the University of Latvia stores the herbariums of this plant from both Latvia and Estonia in the Botanical and mycological collections. Here is both the oldest collected herbarium on the Staburags and the last one collected there in 1961.
Alpine butterwort herbariums at the Museum of the University of Latvia
Keywords: botany; alpu kreimule; alpu taucene; Pinguicula alpina L.; Staburags; ledus laikmeta relikts; herbārijs; Research Subject Categories::NATURAL SCIENCES::Biology; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History of science